2022
DOI: 10.1007/s11686-022-00622-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Geographic Distribution of Dog Tick Species in Sri Lanka and the Life Cycle of Brown Dog Tick, Rhipicephalus sanguineus Under Laboratory Conditions

Abstract: Background: Tick infestations and tick-borne diseases have become a major emerging health concern of dogs in Sri Lanka. Information about tick species infesting dogs and their geographic distribution in Sri Lanka is largely unknown. Here we determined the tick species infesting the dogs and their distribution, and described the life cycle parameters of the dominant dog tick species under laboratory conditions.Methods: An island-wide, cross-sectional survey of tick species infesting the domestic dog was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Lotfi et al (2021) have identified seven species of hard ticks in the cattle of in Jijel Province (northeastern Algeria). Bandaranayaka et al (2022) have reported eight species of brown dog ticks belonging to five genera and noted that the species diversity of brown dog ticks varies in different climatic regions of Sri Lanka.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lotfi et al (2021) have identified seven species of hard ticks in the cattle of in Jijel Province (northeastern Algeria). Bandaranayaka et al (2022) have reported eight species of brown dog ticks belonging to five genera and noted that the species diversity of brown dog ticks varies in different climatic regions of Sri Lanka.…”
Section: Resultsmentioning
confidence: 99%
“…Ticks acts as potential vector along with reservoirs of infectious agents (Pasteurella multocida, Brucella abortus and Salmonella typhimurium) in animals and man (Rony et al, 2010). Bandaranayaka et al (2022) reported that tick infestations and tick-borne diseases have become a major emerging health concern of dogs in Sri Lanka. Ticks infest mostly all types of domestic animals and acts as vectors for the transmission of tick-borne infections in human and animal population worldwide (de la Fuentem et al, 2017;Iqbal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, tick species Rhipicephalus sanguineus tick species and the Ctenocephalides felis flea species (cat flea) are the most common pests affecting dogs and cats [ 4 5 6 ]. The entire life cycle of ticks ( Rhipicephalus sanguineus ) occurs on dog hosts [ 7 ] and be completed in 70-126 days under normal environmental conditions and host availability [ 8 ], whereas the life cycle of fleas mostly occurs outside dogs [ 9 ]. The female fleas can produce 40-50 eggs per day and average of 1,350 eggs over a 50 day period [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an account of their propensity to transmit pathogens, including bacteria, viruses, and protozoan parasites, ticks rank second among arthropods in tropical regions behind mosquitoes (Ariyarathne et al 2016 ). Only a few of the 106 tick species (Bandaranayaka et al 2022 ) discovered in India serve as carriers of disease pathogens. In Kerala, at least 24 different species of ticks have been reported belonging to the genera Amblyomma , Dermacentor , Haemaphysalis , and Rhipicephalus .…”
Section: Introductionmentioning
confidence: 99%